Preparation for Year 10 formal - Fuks, Suzon 1959- (1996)
1. Leg waxing, beauty parlour, Bondi junction -- 2. Making up, beauty parlour -- 3. At the hairdresser -- 4. At home with Mum and friend -- 5. Dressing up in her Mum's room -- 6. At home with Dad -- 7. Visiting the neighbour -- 8. Cocktail party at a friend's
Condition: good.
Title from accession record.
Also available online
Keywords: High school graduates -- New South Wales -- Photographs; Proms; Teenage girls -- Photographs